The royal charter for incorporating the Hudson's Bay Company [electronic resource] : granted by His Majesty King Charles the Second, in the twenty-second year of his reign, A.D. 1670. - Hudson's Bay Company. (London : Printed by R. Causton and Son, ., 1816)
Marginal notes. Electronic reproduction. Mode of access: Internet. 44